The Emergence of Dual-Identity Social Entrepreneurship: Its Boundaries and Limitations. Issue 1 (2nd January 2016) - Busenitz, Lowell W.; Sharfman, Mark P.; Townsend, David M.; Harkins, Jason A.
Abstract: This paper delineates the conceptual domain of dual-identity social entrepreneurship (DISE) and grounds its components theoretically. DISE entails the creation of ventures whose business model is designed by individual founders to create demonstrable and continued public value from strategic actions while simultaneously creating continued economic value. Because the growing interest in social entrepreneurship spans academic areas, boundaries are established among DISE and four related areas: i.e. conventional entrepreneurship, non-governmental organizations which engage in economic transactions, individual social activism, and corporate social performance. This paper proposes key research questions, discusses the conceptualization's theoretical implications and provides a research agenda.